1981
DOI: 10.1111/j.1471-4159.1981.tb01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Sulfatidase for the Reliable Diagnosis of Metachromatic Leukodystrophy

Abstract: A simple assay technique for the determination of sulfatidase activity in leukocytes has been developed for the reliable diagnosis of metachromatic leukodystrophy (MLD). Sulfatide is tritiated in sphingosine and fatty acid by reduction with [3H]sodium borohydride in alkali in the presence of palladium chloride. This labeled natural substrate for aryl sulfatase A (AsA) is hydrolyzed by normal human leukocytes in 25 mM-acetate buffer, pH 5.0, in the presence of 0.3% sodium taurodeoxycholate. The enzyme activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Eleven of these were found in a screening for MLD heterozygotes among healthy adults from a small Jewish community (the Habbanite community) in which a very high incidence of MLD had been found (1175 live births) [Zlotogora et al, 1980;Schaap et al, 19811. There are also reports of persons with very low ASA activity who are not affected with MLD but had various neurological manifestations and are sometimes referred to as atypical MLD variants (Table 11) [Dubois et al, 1980;Raghavan et al, 1981;Butterworth et al, 1978;Weiter et al, 19801. In some of these individuals low activity of arylsulfatase B was noted in addition to the low ASA activity [Raghavan, 19811.…”
Section: Arylsulfatase Amentioning
confidence: 96%
“…Eleven of these were found in a screening for MLD heterozygotes among healthy adults from a small Jewish community (the Habbanite community) in which a very high incidence of MLD had been found (1175 live births) [Zlotogora et al, 1980;Schaap et al, 19811. There are also reports of persons with very low ASA activity who are not affected with MLD but had various neurological manifestations and are sometimes referred to as atypical MLD variants (Table 11) [Dubois et al, 1980;Raghavan et al, 1981;Butterworth et al, 1978;Weiter et al, 19801. In some of these individuals low activity of arylsulfatase B was noted in addition to the low ASA activity [Raghavan, 19811.…”
Section: Arylsulfatase Amentioning
confidence: 96%
“…substrate, nitrocatechol sulfate (ASA-NCS). The assay method using the natural substrate, cerebroside sulfate (ASA-CS), has been shown to have a distinct advantage over the one that utilizes ASA-NCS in determining ASA activity in the presence of arylsulfatase B (ASB), and for the identification of heterozygotes (Raghavan et al 1981). A second study was therefore undertaken, in which a large number of psychiatric patients were screened using less stringent selection criteria.…”
Section: Leukocyte Asamentioning
confidence: 99%
“…This discrepancy necessitates more extensive screening studies with more rigorously standardized assay systems. Our study, for example, has clearly indicated a poor correlation between the two assay systems, using natural substrate (sulfatide) and synthetic substrate (nitrocatechol sulfate) (Shah et al, 1985); and it has also been indicated that, for determining heterozygosity, assay systems using natural substrate appears to provide more reliable results than assay using synthetic sulfate (Raghavan et al, 1981). Differences in populations may constitute yet another source of variation, since variations in gene frequency for the pseudodeficiency allele (ASAp) among different population groups have been noted (e.g., 13.7 and 12.1% for the Arab population, reported by Bach's group Schaap et al, 1981, Herz andBach, 1984, vs 7% for the German population, reported by Propping (1986).…”
Section: 69mentioning
confidence: 99%
“…Metachromatic leukodystrophy (MLD) and globoid cell leukodystrophy (Krabbe disease) are associated with a deficiency in the lysosomal hydrolases arylsulfatase A (ASA) and galactocerebroside 3-galactosidase (cerebrosidase), respectively. Assays of ASA and cerebrosidase activities in leukocytes have been routinely used as a diagnostic tool for determining the homozygous or heterozygous states for MLD (Percy and Brady, 1968;Pilz, 1972;Raghavan et al, 1981;Shah et at., 1985) or Krabbe disease (Suzuki et al, 1972;Poulos and Pollard, 1976). Leukocyte fractions contain mixed cell types that contain different hydrolase activity.…”
Section: Introductionmentioning
confidence: 99%